Kajian dan Induksi Tunas Tanaman Anggur Merah (Vitis vinifera L. var. Prabu Bestari) dengan Beberapa Jenis Sitokinin Secara In Vitro - PEBRIYANI, KADEK; DWIYANI, RINDANG; DARMAWATI, IDA AYU PUTRI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2020)
Study of Sterilization and Induction of Red Grape Shoots ( Vitis vinifera  L. var. Prabu Bestari) with Several Types of Cytokinins  In Vitro This study aims to determine the most suitable sterilization method for the sterilization of red grape explants and to determine the effect of giving growth regulators BAP, 2iP, and TDZ in the induction of red grape shoots. This research was conducted from January to June 2020 at the Tissue Culture Laboratory, Faculty of Agriculture, Udayana University. The design used in this study used a completely randomized design (CRD). The parameters observed in this study were the percentage of contamination, when the shoots appeared, when the roots appeared, the percentage of shoot growth explants, the percentage of root growth explants, and the percentage of leaf growth explants. This research is discussed descriptively. The results of the analysis of the research on the sterilization method showed that the sterilization method I through the maintenance of mother plants with 80% mankozeb and the use of clorox immersion in gradual concentrations was able to reduce the percentage of contamination to 61.2% and the use of TDZ 1 ppm growth regulators in combination with 0.01 ppm NAA on WPM medium was able to induce shoots and roots in red wine explants.